2013
DOI: 10.1128/aac.02056-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In Vitro Antifungal Activities of Efinaconazole and Currently Available Antifungal Agents against a Variety of Pathogenic Fungi Associated with Onychomycosis

Abstract: Onychomycosis is a common fungal nail infection in adults that is difficult to treat. The in vitro antifungal activity of efinaconazole, a novel triazole antifungal, was evaluated in recent clinical isolates of Trichophyton rubrum, Trichophyton mentagrophytes, and Candida albicans, common causative onychomycosis pathogens. In a comprehensive survey of 1,493 isolates, efinaconazole MICs against T. rubrum and T. mentagrophytes ranged from <0.002 to 0.06 g/ml, with 90% of isolates inhibited (MIC 90 ) at 0.008 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
68
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 22 publications
16
68
3
Order By: Relevance
“…Similarly, efinaconazole was 8-fold more active than clotrimazole against C. albicans ATCC 10231 (MICs of 0.00098 and 0.0078 g/ml, respectively). The two strains showed typical susceptibilities to the antifungals tested, consistent with previous findings for these species (6,9).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, efinaconazole was 8-fold more active than clotrimazole against C. albicans ATCC 10231 (MICs of 0.00098 and 0.0078 g/ml, respectively). The two strains showed typical susceptibilities to the antifungals tested, consistent with previous findings for these species (6,9).…”
supporting
confidence: 90%
“…Onychomycosis and other superficial mycoses are caused mainly by dermatophytes (e.g., Trichophyton rubrum and Trichophyton mentagrophytes) and yeast (e.g., Candida albicans). Efinaconazole possesses similar or higher antifungal activity against T. rubrum and T. mentagrophytes (MIC range, 0.00098 to 0.031 g/ml) and a broader spectrum of activity than those of currently marketed antifungals used in onychomycosis (6). We investigated the effects of efinaconazole on fungal ergosterol biosynthesis and dermatophyte hyphal morphology.…”
mentioning
confidence: 99%
“…One limitation of this study is that we did not measure the in vitro activity of other azoles against these isolates. However, the luliconazole MIC range, MIC 50 and MIC 90 values, and GM MICs that were measured in the current study compared favorably those reported in the literature for other azoles against dermatophytes, including itraconazole, voriconazole, posaconazole, ketoconazole, and the investigational agents efinaconazole and ravuconazole (Table 3) (15)(16)(17)(18)(19)(20). Although direct in vitro comparisons with newer azoles are warranted, none of these other azoles, except for itraconazole, currently have an FDA-approved indication for the treatment of onychomycosis.…”
supporting
confidence: 71%
“…For many years, griseofulvin was the only approved systemic antidermatophytic agent (4). However, nowadays, many potent antifungal agents are available for the treatment of dermatophytosis, such as allylamines and triazoles, which have more potent activity and fewer side effects (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The expansion of information on in vitro susceptibility testing of dermatophytes to new antifungal agents will help in the selection and development of antifungal drug regimens.…”
mentioning
confidence: 99%